Professionalism Of Mathematics Subject Teachers In An Effort To Improve The Quality Of Education - Nahiya Nurul Aulia; Anisa Putri Zalya (Pusat Riset dan Inovasi Nasional, 2024)
Education is a very important aspect for every individual in their daily survival. Sometimes people say that education is the path to success, educated people will be very good at controlling emotions and thoughts, but the quality of education in Indonesia is still very low when compared to foreign countries. One of the factors that affects the quality of education in Indonesia is unprofessional teachers. Teachers as educators and instructors are the main factor in realizing educational success. Without active involvement from teachers, education will decline sharply. Therefore, teachers must be professional and have teacher competencies such as personality competence, pedagogical competence, social competence and professional competence to improve the quality of education. So, how do you become a professional teacher, especially a mathematics teacher? Professional teachers have excellent service quality and are recognized by society, have a unique group of scientific fields in carrying out their professional services, carry out deliberate and systematic preparation. The use of learning methods and media must be appropriate, not monotonous, and supported by facilities and infrastructure so that educational goals can be achieved